Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/cancers13246339
|View full text |Cite
|
Sign up to set email alerts
|

New Trends in the Detection of Gynecological Precancerous Lesions and Early-Stage Cancers

Abstract: The prevention and early diagnostics of precancerous stages are key aspects of contemporary oncology. In cervical cancer, well-organized screening and vaccination programs, especially in developed countries, are responsible for the dramatic decline of invasive cancer incidence and mortality. Cytological screening has a long and successful history, and the ongoing implementation of HPV triage with increased sensitivity can further decrease mortality. On the other hand, endometrial and ovarian cancers are charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 183 publications
(183 reference statements)
0
10
0
Order By: Relevance
“…Although the prognostic impact of this condition has not been well investigated to date, attention is needed. Furthermore, blinded D&C may be insufficient to detect focal anomalies of the endometrium because blind sampling can sometimes be not comprehensive 11,21 . Chen et al reported that different uterine cavity surgeries may interfere with the assessment of the lesion's MI on MRI 10 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the prognostic impact of this condition has not been well investigated to date, attention is needed. Furthermore, blinded D&C may be insufficient to detect focal anomalies of the endometrium because blind sampling can sometimes be not comprehensive 11,21 . Chen et al reported that different uterine cavity surgeries may interfere with the assessment of the lesion's MI on MRI 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, blinded D&C may be insufficient to detect focal anomalies of the endometrium because blind sampling can sometimes be not comprehensive. 11,21 Chen et al reported that different uterine cavity surgeries may interfere with the assessment of the lesion's MI on MRI. 10 Therefore, our study chose MRI-based noninvasive examination to differentiate precancerous or malignant from benign endometrial lesions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the early detection of gynecologic malignancies remains a challenge. For instance, although CA-125 is seen as one of the most promising biomarkers in epithelial ovarian cancers, 20% of tumors are missed in initial screenings [36][37][38]. The combination of promising biomarkers is an auspicious strategy to achieve higher diagnostic precision and reliability with respect to clinical applicability.…”
Section: Discussionmentioning
confidence: 99%